2013
DOI: 10.1002/clen.201100472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pumice and Sand on the Sustainability of Granular Iron Beds for the Aqueous Removal of CuII, NiII, and ZnII

Abstract: Running Title: Admixing pumice and sand to reactive Fe 0 sustains long-term metal removal. Acronym List PRB Permeable Reactive Barrier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 62 publications
1
19
1
Order By: Relevance
“…The next step was the demonstration that the volumetric expansive nature of iron corrosion was the main cause of system clogging as Fe 0 is corroded by water (Noubactep 2010a(Noubactep , 2013dNoubactep and Caré 2010a;Noubactep et al 2010;Noubactep and Caré 2011;Bilardi et al 2013a). As a consequence, it was established that admixing non-expansive additive (MnO 2 , pumice, sand) to Fe 0 is a pre-requisite for sustainable filters.…”
Section: The Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step was the demonstration that the volumetric expansive nature of iron corrosion was the main cause of system clogging as Fe 0 is corroded by water (Noubactep 2010a(Noubactep , 2013dNoubactep and Caré 2010a;Noubactep et al 2010;Noubactep and Caré 2011;Bilardi et al 2013a). As a consequence, it was established that admixing non-expansive additive (MnO 2 , pumice, sand) to Fe 0 is a pre-requisite for sustainable filters.…”
Section: The Way Forwardmentioning
confidence: 99%
“…In essence, the next work consists in building a database for the rate constant of Fe 0 materials under field conditions. Some laboratory and field designs were recently published (Noubactep 2011d;Noubactep et al 2012a;Caré et al 2013;Bilardi et al 2013aBilardi et al , 2013bNdé-Tchoupé et al 2015;Tepong-Tsindé et al 2015a;Li et al 2016 Appl Water Sci (2017) 7:4177-4196 4189 monitoring: (1) the aqueous Fe concentration, (2) the pH value, (3) the water flow velocity, and (4) the electric conductivity. Intermittently adding a contaminant, including an indicator like methylene blue (e.g., 250 mL every 2 months) and monitoring its behavior would help to discuss the efficiency of the investigated systems.…”
Section: The Way Forwardmentioning
confidence: 99%
“…The research community must realize now that this misconception has created a non-precedent confusion [35,44,45,[55][56][57][58][59][60]. Over the last decade, isolated researchers [8,23,[61][62][63][64][65][66][67][68] have corrected the mistake but the large majority is still confounding 'reduction in the presence of Fe 0 (including indirect reduction) and 'reduction by Fe 0 (direct reduction-electrons from Fe 0 ) [1][2][3]69,70].…”
Section: Source Of the Misconceptionmentioning
confidence: 99%
“…It has been unambiguously demonstrated that all tools used to accelerate lab-scale experiments collectively impair the reliability of the obtained test results [35,[65][66][67]. Relevant tools include adding oxidizing agents to accelerate corrosion [58], increasing flow velocity [34] and using Fe 0 of smaller particle sizes and/or rapid small-scale column tests [65].…”
Section: (Section 2)mentioning
confidence: 99%